2012
DOI: 10.1177/0956797612439067
|View full text |Cite
|
Sign up to set email alerts
|

Birth-Cohort Effects in the Association Between Personality and Fertility

Abstract: The present study investigated whether associations between individuals' personality traits and whether they have children have been modified by birth-cohort effects in the 20th-century United States. Participants were from the Midlife Development in the United States study (n = 6,259) and the Wisconsin Longitudinal Study (n = 3,994) and were born between 1914 and 1974. Data on personality traits of the Five Factor model and fertility history were collected in adulthood. Higher levels of openness to experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 28 publications
3
48
1
Order By: Relevance
“…Those higher in Openness are more likely to postpone or forgo marriage (Lundberg 2012), and to have children later in life (Tavares 2008). Jokela (2012) found high Openness had a stronger association with fertility for younger birth cohorts, reflecting recent advances in gender equality and increasing acceptance of non-traditional lifestyles. Tavares (2008) suggested that much of the difference in timing of first birth between more and less educated women may be due to a subgroup of more Open women within the educated group strongly postponing childbirth and therefore pushing up the average age to create a 'fertility gap'.…”
Section: Openness To Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Those higher in Openness are more likely to postpone or forgo marriage (Lundberg 2012), and to have children later in life (Tavares 2008). Jokela (2012) found high Openness had a stronger association with fertility for younger birth cohorts, reflecting recent advances in gender equality and increasing acceptance of non-traditional lifestyles. Tavares (2008) suggested that much of the difference in timing of first birth between more and less educated women may be due to a subgroup of more Open women within the educated group strongly postponing childbirth and therefore pushing up the average age to create a 'fertility gap'.…”
Section: Openness To Experiencementioning
confidence: 99%
“…In women, higher Agreeableness is associated with more children, earlier childbirth, and a higher probability of marriage, regardless of birth cohort or education level (Jokela 2012;Tavares 2008), but it does not seem to have this relationship for men although more agreeable men get married and have children earlier than less agreeable men (Jokela et al 2011). Lower Agreeableness predicted greater decisional ambivalence towards parenting in young adults and adolescents of both genders (Pinquart et al 2008), andMiller (1992) found that the related traits of Nurturance and Affiliation were positively associated with childbearing motivation, again in both genders.…”
Section: Agreeablenessmentioning
confidence: 99%
“…Openness to experience (intellect; creativity) was negatively related to fertility in British women, partly because it positively predicted educational uptake and fertility postponement [94]. This has been echoed in males [94] and increasingly in younger birth cohorts for both sexes [95], though inconsistently [96]. Agreeableness (cooperativeness; empathy) predicts higher fertility at least in females [95], also including reproductive acceleration [94].…”
Section: (D) Personalitymentioning
confidence: 99%
“…Conscientiousness seems to decrease fertility, for example, in Norwegian women across 40 years of data [92] and in British panel data [94] conscientious women postponed childbearing. In Finnish data, the association increased in later cohorts and in both sexes [95]. Openness to experience (intellect; creativity) was negatively related to fertility in British women, partly because it positively predicted educational uptake and fertility postponement [94].…”
Section: (D) Personalitymentioning
confidence: 99%
“…showing that low scorers on conscientiousness tend to have more children (e.g., Jokela, Hintsa, Hintsanen, & Keltikangas-Järvinen, 2010;Jokela, Alvergne, Pollet, & Lummaa, 2011;Jokela, 2012 Berg, Lummaa, Lahdenperä, Rotkirch and Jokela (2014) found that lower conscientiousness is linked to more children and grandchildren in both sexes.…”
Section: Personality Welfare and Differential Reproductionmentioning
confidence: 99%